Mixed-phase molybdenum diselenide adsorption material as well as preparation method and application thereof
By using mixed-phase molybdenum diselenide material, the adsorption performance of molybdenum diselenide is improved by using the combination of 1T phase and 2H phase, the problem of insufficient active sites in the prior art is solved, and the efficient removal of lead ions in water is achieved and selective adsorption.
Patent Information
- Application Number
- CN202411444709.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-17
AI Technical Summary
The existing molybdenum diselenide material consists of semiconductor 2H phase. The inert surface leads to a limited number of active sites, resulting in insufficient adsorption capacity of lead ions, making it difficult to efficiently remove lead pollution in water.
The mixed-phase molybdenum diselenide adsorption material consisting of metal phase (1T phase) and semiconductor phase (2H phase). The nanosheet-layer molybdenum diselenide material is prepared through solvothermal reaction to improve its adsorption performance on lead ions. .
It achieves high selective removal of lead ions in water bodies, fast adsorption speed, high capacity and good selectivity, and is suitable for lead pollution repair in natural water bodies and industrial wastewater.
Smart Images

Figure CN119140054A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental functional materials and water treatment, and in particular to a mixed-phase molybdenum diselenide adsorption material and a preparation method and application thereof. Background Art
[0002] Lead is a toxic heavy metal. The use of lead-containing products and industrial production (such as batteries, mining and smelting, photovoltaic technology, etc.) have caused lead pollution in natural water resources (surface water, groundwater, drinking water, etc.) and industrial wastewater. In particular, the aging of lead-containing materials (such as water supply networks, solder, etc.) has made it difficult to obtain clean water in many areas. Lead is bioaccumulative and neurotoxic. Its occurrence and long-term exposure in water bodies pose serious hazards to ecosystems and human health. Therefore, the removal of lead in water bodies is of great significance.
[0003] The main technologies for removing lead ions from water bodies include ion exchange, membrane separation, adsorption and electrochemical treatment. Among them, the adsorption method has attracted widespread attention due to its low cost and simple operation. For the adsorption and removal of lead ions, it is particularly important to construct efficient adsorption materials. The main performance indicators include adsorption kinetics, adsorption capacity and selectivity. Molybdenum diselenide is a two-dimensional transition metal chalcogenide material. Studies have shown that chalcogens have a strong affinity for heavy metals, among which selenium may have a stronger binding ability with lead. However, the lead adsorption capacity of molybdenum diselenide is directly related to the active sites on the surface. Conventional bulk molybdenum diselenide materials are composed of semiconductor phases (2H phases), and the inert surface leads to a limited number of active sites. Summary of the invention
[0004] The present invention aims at the deficiencies in the prior art and provides a mixed-phase molybdenum diselenide adsorption material and a preparation method and application thereof. The adsorption material of the present invention improves the adsorption performance of molybdenum diselenide on lead ions and realizes highly selective removal of lead ions in water.
[0005] The present invention first provides a mixed-phase molybdenum diselenide adsorption material, which consists of two phases: a metal phase (1T phase) and a semiconductor phase (2H phase), wherein the 1T phase is the main crystal phase and the molybdenum diselenide has a nanosheet structure.
[0006] In the mixed-phase molybdenum diselenide adsorption material, the size of the molybdenum diselenide nanosheets is 50-200 nm, preferably 50-100 nm.
[0007] In the mixed-phase molybdenum diselenide adsorption material, the mass percentage of the 1T phase is 40-80%, preferably 70-80%, based on the total mass of the mixed-phase molybdenum diselenide adsorption material.
[0008] The present invention further provides a method for preparing the mixed-phase molybdenum diselenide adsorption material, comprising the following steps: dispersing Na2MoO4·2H2O, selenium powder and NaBH4 in a mixture of anhydrous ethanol and water, and performing a solvothermal reaction to obtain the mixed-phase molybdenum diselenide adsorption material; wherein the mass ratio of the Na2MoO4·2H2O, selenium powder and NaBH4 is 1:0.6~0.7:0.3~0.7.
[0009] The preparation method specifically comprises the following steps: placing Na2MoO4·2H2O and selenium powder in a mixture of anhydrous ethanol and water, adding NaBH4 to disperse and dissolve; then performing a solvothermal reaction to obtain the mixed phase molybdenum diselenide adsorption material; Specifically, the time for dispersing and dissolving is 30 to 40 minutes; the dispersing and dissolving can be performed by mechanical stirring or ultrasonic wave.
[0010] In the above preparation method, the mass ratio of Na2MoO4·2H2O, selenium powder and NaBH4 is 1:0.6~0.7:0.63; more specifically, it can be 1:0.65:0.63, 1:0.65:0.32 or 1:0.65:0.48.
[0011] In the above preparation method, the volume ratio of anhydrous ethanol to water is 0.8-1.2:1, specifically 1:1; The mass volume ratio of the mixture of Na2MoO4·2H2O, anhydrous ethanol and water is 8-9 mg / mL.
[0012] In the above preparation method, the temperature of the solvent thermal reaction is 160-180°C, specifically 180°C; the time is 18-24h, specifically 24h.
[0013] The above-mentioned preparation method further includes the steps of washing and vacuum drying the solid in sequence after the solvent thermal reaction is completed; specifically, the washing is carried out in sequence using water and anhydrous ethanol; the vacuum drying temperature is 50~70°C and the time is 10~15h; more specifically, the vacuum drying temperature is 60°C and the time is 12h.
[0014] The use of the mixed-phase molybdenum diselenide adsorption material in removing lead ions from water also falls within the protection scope of the present invention.
[0015] Finally, the present invention provides a method for removing lead ions from water, comprising the following steps: dispersing the above-mentioned mixed-phase molybdenum diselenide adsorption material in the water to be treated, and separating after adsorption equilibrium.
[0016] In the above method, adsorption is carried out under shaking conditions; The adsorption time is 2 to 60 minutes, specifically 2 to 15 minutes or 8 to 15 minutes; The mass ratio of the mixed phase molybdenum diselenide adsorption material to the lead ions in the water body is 1:0.025-1.5, specifically 1:0.025-0.5; The concentration of lead ions in the water is 5-300 mg / L, specifically 5 mg / L or 20 mg / L; The water body is deionized water, natural water or industrial wastewater.
[0017] In the above method, the water body may also contain at least one of manganese ions, nickel ions, zinc ions, cadmium ions and copper ions; specifically, the concentration of each ion is 10~50mg / L; specifically, it may be 20mg / L.
[0018] In the above method, the pH value of the water body is 4-7.
[0019] Conventional molybdenum diselenide materials are composed of semiconductor 2H phases, which have the advantage of natural stable existence, but are often low in activity, poor in adsorption capacity, and slow in kinetics. The mixed-phase molybdenum diselenide adsorption material provided by the present invention is significantly different from conventional molybdenum diselenide materials. The mixed-phase molybdenum diselenide of 1T phase and 2H phase combines the advantages of the two phases. While ensuring the stability of the material, the reaction activity and adsorption performance of the molybdenum diselenide material are improved by increasing the 1T phase content (from 14% to 77%), fully exposing the adsorption active sites on the surface of the material, and realizing the rapid, efficient and highly selective removal of lead ions in water.
[0020] Compared with conventional molybdenum diselenide materials, the preparation method and structural morphology of the mixed phase molybdenum diselenide adsorption material of the present invention are different. The present invention uses NaBH4 as an electron donor, reduces the formation energy of the 1T phase in molybdenum diselenide by increasing the amount of NaBH4, and constructs a molybdenum diselenide material with a high 1T phase content.
[0021] The mixed-phase molybdenum diselenide adsorption material of the present invention has the advantages of fast adsorption speed, small material consumption, high adsorption capacity, good selectivity, etc. when adsorbing lead ions. At the same time, it has good application effect in natural water bodies and industrial wastewater and has high practical application value.
[0022] The application of the mixed phase molybdenum diselenide adsorption material provided by the present invention in the adsorption and removal of lead ions in water has obvious advantages, which are specifically manifested in the following aspects: 1) Fast adsorption speed and low material consumption: When 0.1 g / L of adsorbent is used, the removal rate of 20 mg / L lead ions is more than 99% within 10 minutes; compared with commercial bulk molybdenum diselenide materials and synthetic 2H phase-based molybdenum diselenide materials, the adsorption kinetics of the 1T phase-based molybdenum diselenide adsorption material in the present invention is significantly accelerated, which is mainly related to the fact that the 1T phase molybdenum diselenide promotes charge migration and exposure of surface active sites; 2) High adsorption capacity: The adsorption capacity of lead ions can reach 945.2 mg / g, which is higher than most metal nano-adsorbents; 3) Good selectivity: The 1T phase-based molybdenum diselenide adsorption material of the present invention can remove lead ions at a rate of more than 99%, while the removal rate of heavy metal ions in five common industrial wastewaters, namely manganese, nickel, zinc, cadmium and copper, is low or almost non-adsorbed; compared with the other five metals, the distribution coefficient of the material for lead ions is 4 to 5 orders of magnitude higher; 4) Great potential for practical application: The removal rate of lead ions with a concentration of 5 mg / L in tap water, lake water, groundwater, seawater and coal-fired power plant wastewater can reach more than 99%, which can be applied to the remediation of actual lead-containing wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope characterization image of the molybdenum diselenide nanosheets prepared in Example 1 and Comparative Example 1.
[0024] Figure 2 Transmission electron microscope characterization images of molybdenum diselenide nanosheets prepared in Example 1 and Comparative Example 1.
[0025] Figure 3 X-ray diffraction patterns of two molybdenum diselenide nanosheets prepared in Example 1 and Comparative Example 1.
[0026] Figure 4 X-ray photoelectron spectra of two molybdenum diselenide nanosheets prepared in Example 1 and Comparative Example 1; Figure 4 a in the figure is the high-resolution Mo 3d spectrum; b is the high-resolution Se 3d spectrum, and c is the result of the ratio of 1T phase and 2H phase in molybdenum diselenide calculated based on the high-resolution spectrum.
[0027] Figure 5 The adsorption kinetics of lead ions by different molybdenum diselenide nanosheets in Example 2; Figure 5 a is the relationship curve between lead ion concentration and adsorption time, and b is the relationship curve between lead ion removal rate and adsorption time.
[0028] Figure 6 This is the adsorption isotherm curve of the mixed-phase molybdenum diselenide nanosheets (high 1T phase content) for lead ions in Example 3 and the Langmuir isotherm model fitting effect.
[0029] Figure 7 The adsorption removal rate (a) and distribution coefficient (b) of the mixed-phase molybdenum diselenide nanosheets (high 1T phase content) in Example 4 for six heavy metal ions, namely manganese, nickel, zinc, cadmium, copper and lead in water, as well as the comparison of the selective adsorption performance of lead with molybdenum disulfide nanosheets (c).
[0030] Figure 8 The adsorption effect and removal rate of lead ions in tap water, lake water, groundwater, seawater and coal-fired power plant wastewater samples by the mixed-phase molybdenum diselenide nanosheets (high 1T phase content) in Example 5 are shown.
[0031] Fig. 9 The adsorption kinetics of lead ions by molybdenum diselenide nanosheets with three different 1T phase contents in Example 1 and Example 6 are specifically the relationship curve between lead ion concentration and adsorption time. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.
[0033] The experimental methods in the following examples are all conventional methods unless otherwise specified.
[0034] The quantitative tests in the following examples were all repeated three times, and the results were averaged.
[0035] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0036] In the following examples, the aqueous solution containing lead ions was prepared from the lead standard solution of the National Research Institute of Nonferrous Metals, the lead standard solution concentration was 1000 mg / L, and the matrix was nitric acid (GSB 04-1742-2004); An aqueous solution containing six heavy metal ions, namely manganese, nickel, zinc, cadmium, copper and lead, was prepared from standard solutions, among which the standard solutions of manganese, nickel, zinc, cadmium, copper and lead were purchased from China National Research Institute of Nonferrous Metals, manganese (GSB 04-1736-2004), nickel (GSB 04-1740-2004), zinc (GSB 04-1761-2004), cadmium (GSB 04-1721-2004), copper (GSB 04-1725-2004) and lead (GSB 04-1742-2004).
[0037] Example 1. Preparation of mixed phase MoSe nanosheets (high 1T phase content) 0.484 g (2 mmol) Na2MoO4·2H2O and 0.316 g (4 mmol) selenium powder were placed in a mixture of 30 mL of anhydrous ethanol and 30 mL of deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:1), and NaBH4 was added for further stirring, dispersion and dissolution for 30 min. Then, a solvothermal reaction was carried out in a reactor at 180°C for 24 h. The mass ratio of Na2MoO4·2H2O, selenium powder and NaBH4 was 1:0.65:0.63. After the reaction, the mixture was cooled to room temperature, and the solid was washed with deionized water and anhydrous ethanol at least 3 times respectively, and vacuum dried at 60°C for 12 h to obtain powdery molybdenum diselenide nanosheets with a high 1T phase content.
[0038] The scanning electron microscope characterization image of the molybdenum diselenide nanosheet prepared in this example is shown in Figure 1 a in the figure shows that it has a typical nanosheet structure with a size of 50~100nm.
[0039] The transmission electron microscope characterization of the molybdenum diselenide nanosheets prepared in this example is shown in Figure 2 a in the figure shows that it has a typical 1T phase MoSe structure.
[0040] The X-ray diffraction pattern of the molybdenum diselenide nanosheets prepared in this example is shown in Figure 3 , which can correspond to the typical crystal planes (002), (100) and (110) of MoSe.
[0041] The X-ray photoelectron spectrum of the MoSe nanosheets prepared in this example is shown in Figure 4 , which can correspond to the high-resolution Mo 3d and Se 3d spectra of typical MoSe, and the corresponding phase ratio can be calculated based on the characteristic peak areas of 1T phase and 2H phase.
[0042] Comparative Example 1: Preparation of mixed phase MoSe nanosheets (high 2H phase content) The material preparation method of this comparative example is substantially the same as that of Example 1, the main difference being that the amount of NaBH4 is adjusted so that the mass ratio of Na2MoO4·2H2O, selenium powder and NaBH4 is 1:0.65:0.16, and the rest of the preparation process and reaction conditions are consistent with those of Example 1, and finally powdery molybdenum diselenide nanosheets with a high 2H phase content are obtained.
[0043] The scanning electron microscope characterization of the molybdenum diselenide nanosheets prepared in this comparative example is shown in Figure 1 b in the figure shows that it has a typical nanosheet structure.
[0044] The transmission electron microscope characterization of the molybdenum diselenide nanosheets prepared in this comparative example is shown in Figure 2 b in the figure shows that it has a typical 2H phase MoSe structure.
[0045] The X-ray diffraction pattern of the molybdenum diselenide nanosheets prepared in this comparative example is shown in Figure 3 , which can correspond to the typical crystal planes (002), (100) and (110) of MoSe.
[0046] The X-ray photoelectron spectrum of the molybdenum diselenide nanosheets prepared in this comparative example is shown in Figure 4 .
[0047] Comparative Example 2: Preparation of MoS2 Nanosheets 1.24 g (NH4)6Mo7O 24 4H2O and 2.28 g CH4N2S were dispersed in 35 mL deionized water, stirred for 30 min, and then transferred to a reactor, where (NH4)6Mo7O 24 The mass ratio of 4H2O and CH4N2S was 1:1.84. After hydrothermal reaction at 180°C for 24 h, the product was cooled to room temperature, washed with deionized water and anhydrous ethanol at least 3 times respectively, and vacuum dried at 60°C for 12 h to obtain powdered molybdenum disulfide nanosheets.
[0048] Example 2: Adsorption kinetics test of lead ions by different molybdenum diselenide nanosheets 10 mg of each of the materials prepared in Example 1 and Comparative Example 1 and the purchased commercial molybdenum diselenide material (McLean, M849297, CAS No.: 12058-18-3) were added to 100 mL of an aqueous solution containing lead ions, and shaken at 180 rpm at room temperature to overcome mass transfer resistance, wherein the lead ion concentration was 20 mg / L and the pH of the water body was about 5 to 6. At 2 min, 5 min, 10 min, 15 min, 20 min, 30 min, 45 min and 60 min of adsorption, the supernatant was taken and analyzed by inductively coupled plasma mass spectrometry to obtain the concentration of residual lead ions in the water body, and then the removal rate of lead ions was obtained.
[0049] It is calculated that after 2min, 5min, 10min, 15min, 20min, 30min, 45min and 60min of adsorption reaction, the removal rates of lead ions in water by mixed-phase MoSe nanosheets (high 1T phase content) are 99.1%, 99.8%, 99.9%, 99.9%, 99.9%, 99.9%, 99.9% and 99.9%, respectively; the removal rates of lead ions in water by mixed-phase MoSe nanosheets (high 2H phase content) are 40.3%, 60.6%, 74.5%, 77.5%, 79.2%, 81.6%, 84.0% and 85.5%, respectively; the removal rates of lead ions in water by commercial MoSe materials are 1.4%, 2.3%, 3.2%, 3.7%, 4.6%, 5.7%, 8.4% and 9.3%, respectively; Figure 5 As shown. It can be seen that the mixed phase MoSe nanosheets (high 1T phase content) have a very fast adsorption rate for lead ions, reaching adsorption equilibrium in about 10 minutes, with a removal rate of more than 99%, and the adsorption effect is significantly stronger than the other two MoSe materials. This is mainly related to the fact that the 1T phase MoSe promotes charge migration and the exposure of surface active sites.
[0050] Example 3. Adsorption isotherm test of mixed phase MoSe nanosheets (high 1T phase content) for lead ions 10 mg of the mixed-phase molybdenum diselenide nanosheets (high 1T phase content) prepared in Example 1 was added to 50 mL of an aqueous solution containing lead ions, and the mixture was shaken at 180 rpm at room temperature to overcome the mass transfer resistance, wherein the lead ion concentration was 20-300 mg / L (20, 50, 100, 150, 200, 250, 300 mg / L), the pH of the water body was about 5-6, and after adsorption for 12 hours to reach saturation, the supernatant was taken and the concentration of remaining lead ions in the water body was analyzed by inductively coupled plasma mass spectrometry to obtain the adsorption capacity of the material for lead ions.
[0051] According to calculations, the saturated adsorption capacity of mixed phase MoSe nanosheets (high 1T phase content) for lead ions in water can reach 945.2 mg / g. Figure 6 shown.
[0052] Example 4. Adsorption selectivity of mixed phase MoSe nanosheets (high 1T phase content) for lead ions 10 mg of the mixed phase molybdenum diselenide nanosheets (high 1T phase content) prepared in Example 1 was added to 50 mL of an aqueous solution containing six heavy metal ions of manganese, nickel, zinc, cadmium, copper and lead, and the ion concentration was 20 mg / L. The solution pH was adjusted to 5-6, and after shaking on a shaker at 180 rpm for 60 min at room temperature, the supernatant was taken and analyzed by inductively coupled plasma mass spectrometry for the remaining heavy metal ion concentration in the water body, and the adsorption removal rate of the material for different heavy metal ions was obtained.
[0053] According to calculations, 60 minutes after the adsorption reaction, the adsorption removal rates of heavy metal ions in water by mixed phase MoSe nanosheets (high 1T phase content) are: manganese ions (6.5%), nickel ions (7.3%), zinc ions (8.0%), cadmium ions (12.7%), copper ions (12.5%), and lead ions (99.2%). The distribution coefficient of lead ions is 4 to 5 orders of magnitude higher than that of other heavy metal ions, such as Figure 7 As shown in ab.
[0054] This result indicates that the mixed-phase MoSe nanosheets (high 1T phase content) in the present invention have extremely high selective adsorption capacity for lead ions in the presence of other heavy metal ions.
[0055] The experimental method is the same as above. Take 10 mg of the two materials and add 20 mg / L lead ion solution respectively. Then remove and measure the remaining lead ion concentration after adsorption for 60 minutes to obtain the adsorption amount of the material and calculate the adsorption distribution coefficient. Figure 7 From c in FIG. 1 , it can be seen that compared with the removal rate and distribution coefficient of lead ions of molybdenum disulfide materials, the mixed-phase molybdenum diselenide nanosheets (high 1T phase content) in the present invention exhibit stronger lead ion selectivity.
[0056] Example 5: Adsorption test of lead ions in actual water by mixed phase molybdenum diselenide nanosheets (high 1T phase content) 10 mg of the mixed phase molybdenum diselenide nanosheets (high 1T phase content) prepared in Example 1 were added to 50 mL of tap water, lake water, groundwater, seawater and coal-fired power plant wastewater samples containing lead ions, and the pH value of the water sample was 6-7 (water samples collected in the actual environment were used and prepared using a lead standard solution). Referring to the concentration level of lead pollution in the real environment, the lead ion concentration was set to 5 mg / L. After oscillating at room temperature for 60 minutes to ensure that the material reached adsorption equilibrium, the supernatant was taken and the remaining lead ion concentration in the water was analyzed by inductively coupled plasma mass spectrometry to obtain the adsorption removal rate of lead ions.
[0057] It has been calculated that the removal rates of lead ions in tap water, lake water, groundwater, seawater and coal-fired power plant wastewater samples with a lead ion concentration of 5 mg / L by mixed-phase molybdenum diselenide nanosheets (high 1T phase content) are 99.7%, 98.7%, 99.3%, 99.2% and 98.8%, respectively. Figure 8 As shown, it is proved that the mixed-phase molybdenum diselenide nanosheets (high 1T phase content) of the present invention can be used for the remediation of lead pollution in actual environmental water bodies.
[0058] Example 6. Preparation of mixed phase MoSe nanosheets (different 1T phase contents) The specific synthesis conditions are similar to those in Example 1, except that the mass ratios of Na2MoO4·2H2O, selenium powder and NaBH4 are adjusted to 1:0.65:0.32 and 1:0.65:0.48, respectively, and two molybdenum diselenide nanosheets with different 1T phase contents are obtained by reaction. According to the characteristic peak areas of the 1T phase and the 2H phase, the 1T phase ratios of the two molybdenum diselenide nanosheets are calculated to be 41% and 59%, respectively.
[0059] The molybdenum diselenide nanosheets with high 1T phase content prepared in Example 1 and the molybdenum diselenide nanosheets with different 1T phase contents prepared in Example 6 were taken to carry out the adsorption kinetics test of lead ions, and the specific implementation method was the same as that in Example 2. For the molybdenum diselenide nanosheets with a 1T phase content of 41%, the lead ion concentration in the lead ion solution with an initial concentration of 20 mg / L became 6.74 mg / L, 3.32 mg / L, 1.67 mg / L, 0.66 mg / L, 0.33 mg / L, 0.19 mg / L, 0.06 mg / L, and 0.01 mg / L respectively after the adsorption reaction occurred for 2 min, 5 min, 10 min, 15 min, 20 min, 30 min, 45 min, and 60 min. It has been calculated that the removal rates of lead ions in water by molybdenum diselenide nanosheets with a 1T phase content of 41% are 66.3%, 83.4%, 91.6%, 96.7%, 98.3%, 99.1%, 99.7% and 99.9% respectively.
[0060] For MoSe nanosheets with 1T phase content of 59%, the lead ion concentration in the lead ion solution with an initial concentration of 20 mg / L changes to 1.84 mg / L, 0.65 mg / L, 0.27 mg / L, 0.05 mg / L, 0.03 mg / L, 0.01 mg / L, 0.002 mg / L, and 0.001 mg / L, respectively, after the adsorption reaction occurs for 2 min, 5 min, 10 min, 15 min, 20 min, 30 min, 45 min, and 60 min. It is calculated that the removal rates of lead ions in water bodies by MoSe nanosheets with 1T phase content of 41% are 90.8%, 96.7%, 98.6%, 99.7%, 99.8%, 99.9%, 99.9%, and 99.9%, respectively. Fig. 9 As shown. It can be seen that the increase in the proportion of 1T phase in the mixed phase MoSe nanosheets helps to increase the adsorption rate of lead ions. The adsorption effect of MoSe nanosheets with the highest 1T phase content (77%) is significantly stronger than that of the other two MoSe materials. This is mainly related to the fact that 1T phase MoSe promotes charge migration and the exposure of surface active sites.
Claims
1. A mixed phase molybdenum diselenide adsorption material, characterized in that: The mixed-phase molybdenum diselenide adsorption material consists of two phases, a metal phase (1T phase) and a semiconductor phase (2H phase), wherein the 1T phase is the main crystal phase and the molybdenum diselenide is in the form of a nanosheet structure.
2. The mixed phase molybdenum diselenide adsorption material according to claim 1, characterized in that: The size of MoSe nanosheets is 50~200nm.
3. The mixed phase molybdenum diselenide adsorption material according to claim 1 or 2, characterized in that: Based on the total mass of the mixed-phase molybdenum diselenide adsorption material, the mass percentage of the 1T phase is 40-80%, preferably 70-80%.
4. A method for preparing the mixed-phase molybdenum diselenide adsorption material according to any one of claims 1 to 3, comprising the following steps: dispersing Na2MoO4·2H2O, selenium powder and NaBH4 in a mixture of anhydrous ethanol and water, and performing a solvothermal reaction to obtain the mixed-phase molybdenum diselenide adsorption material; wherein, The mass ratio of the Na2MoO4·2H2O, selenium powder and NaBH4 is 1:0.6~0.7:0.3~0.
7.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the Na2MoO4·2H2O, selenium powder and NaBH4 is 1:0.6~0.7:0.
63.
6. The preparation method according to claim 4 or 5, characterized in that: The volume ratio of anhydrous ethanol to water is 0.8-1.2:1; The mass volume ratio of the mixture of Na2MoO4·2H2O, anhydrous ethanol and water is 8-9 mg / mL.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The temperature of the solvent thermal reaction is 160-180° C. and the time is 18-24 hours.
8. Use of the mixed-phase molybdenum diselenide adsorption material according to any one of claims 1 to 3 in removing lead ions from water.
9. A method for removing lead ions from water, comprising the following steps: dispersing the mixed-phase molybdenum diselenide adsorption material according to any one of claims 1 to 3 in the water to be treated, and separating after adsorption equilibrium.
10. The method according to claim 9, characterized in that: The adsorption time is 2 to 60 minutes; The mass ratio of the mixed phase molybdenum diselenide adsorption material to the lead ions in the water body is 1:0.025-1.5, preferably 1:0.025-0.5; The concentration of lead ions in the water is 5-300 mg / L; The water body is deionized water, natural water or industrial wastewater.
